DIRECTIONS FOR ADAPTATION OF FINANCIAL STATEMENTS TO INTERNATIONAL STANDARDS (Academicia Globe: Inderscience Research, 2023)
In the conditions of modernization of the economy, detailed information on the different aspects of the existing financial reporting forms from the international financial reporting forms and the order of their preparation is provided.